Mechanical behavior of ECC-encased CFST columns subjected to eccentric loading. (1st May 2018) - Cai, Jingming; Pan, Jinlong; Lu, Cong
Highlights: This paper presented the results of experimental study of ECC-encased CFST columns subjected to eccentric loading. The influence of different parameters were discussed in this paper. The failure processes and failure mechanism for each column were investigated. Abstract: To increase the durability and fire resistance of concrete filled steel tube (CFST) columns, engineered cementitious composite (ECC)-encased CFST columns were proposed in this paper. Seven ECC-encased CFST columns with different parameters were tested, the parameters examined included eccentricity ratio, stirrup reinforcement ratio, longitudinal reinforcement ratio and thickness of inner steel tube. The results of the experimental study indicate that the proposed composite column exhibited both superior ductility and high strength under different eccentricity. Three typical failure modes can be observed depending on different eccentricity ratios, which were compression-controlled failure mode, balanced failure mode and tension-controlled failure mode. The thickness of steel tube had significant effects on both load carrying capacity and ductility of ECC-encased CFST columns. The longitudinal reinforcement could enhance the rigidity and loading carrying capacity of ECC-encased CFST columns, and the stirrup could improve the ductility of the composite column. Finally, the failure processes for typical columns were also investigated based on the strain analysis.